APPLYING HIGHER ORDER THINKING SKILLS (HOTS) PEDAGOGY: A CASE STUDY OF AN EFL CORE TEACHER - Saraswati, Nais; Inderawati, Rita; Vianty, Machdalena (English Review: Journal of English Education, 2023)
HOTS (Higher Order Thinking Skills) is an indispensable skill crucial for meeting the future demands of the 21st century. It plays a fundamental role in encouraging students to think critically, be more creative, and effectively solve problems. HOTS pedagogy encompasses the entire teaching and learning process, encompassing the selection of teaching and learning strategies as well as the creation of tasks and assessments based on HOTS principles. This study aimed to explore how an EFL (English as a Foreign Language) core teacher understands and implements HOTS pedagogy in the EFL classroom. Qualitative research in the form of narrative inquiry was employed for this investigation, with a single participant chosen through criteria sampling. Data collection was carried out through semi-structured interviews, and data analysis utilized the constant-comparative method. The study's findings shed light on the teacher's planning when implementing HOTS pedagogy, the teaching techniques employed to foster HOTS skills in students, and the utilization of HOTS-based assessments. Additionally, the findings identified an issue with the arrangement of operational verbs in the EFL core teacher's planning and revealed that the use of discovery learning as a teaching technique created disparities in understanding the lesson between passive and dominant students.